2001
DOI: 10.1016/s0008-6215(01)00235-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and NMR spectroscopy of nine stereoisomeric 5,7-diacetamido-3,5,7,9-tetradeoxynon-2-ulosonic acids

Abstract: Derivatives of 5,7-diamino-3,5,7,9-tetradeoxynon-2-ulosonic acids are essential constituents of some bacterial polysaccharides and glycoproteins. In order to establish reliably the configuration of the natural sugars, nine stereoisomeric 5,7-diacetamido-3,5,7,9-tetradeoxynon-2-ulosonic acids were synthesized, including di-N-acetyl-legionaminic and -pseudaminic acids (the D-glycero-D-galacto and L-glycero-L-manno isomers, respectively) and their isomers at C-4, C-5, C-7, and C-8 having the L-glycero-D-galacto, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
95
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 27 publications
13
95
0
Order By: Relevance
“…12A). The 1 H and 13 C chemical shifts of the 8-epi-legionaminic acid residue A minor form assigned in this study were in good agreement with those reported previously for the chemically synthesized 8-epi-legionaminic acid (41).…”
Section: Assignment Of 8-epi-legionaminic Acid Residues a And E-supporting
confidence: 91%
See 1 more Smart Citation
“…12A). The 1 H and 13 C chemical shifts of the 8-epi-legionaminic acid residue A minor form assigned in this study were in good agreement with those reported previously for the chemically synthesized 8-epi-legionaminic acid (41).…”
Section: Assignment Of 8-epi-legionaminic Acid Residues a And E-supporting
confidence: 91%
“…This large chemical shift perturbation (⌬␦ ϭ ϳ4.5 ppm) likely reflects the differences in the attachment at the 8th carbon. The 21.24 ppm of the C9 carbon of residue A minor form was consistent with having no attachment at the 8th carbon because the chemically synthesized 8-epi-legionaminic acid monosaccharide also has a C9 chemical shift at ϳ20.0 ppm (41).…”
Section: Assignment Of 8-epi-legionaminic Acid Residues a And E-mentioning
confidence: 78%
“…Upon removal of the CMP group by acid hydrolysis to form III, J 7,8 was determined to be 7.6 Hz (supplemental Fig. S2), in good agreement with the value reported for legionaminic acid (33). To establish the location of the acetamidino group, II was suspended in 95% H 2 O (5% D 2 O), and the pH was lowered through the addition of diluted DCl (pH 3.7) (18).…”
Section: Hilic-ms Purification Of C Coli Vc167 Cmp-activated Metabolsupporting
confidence: 71%
“…Therefore, the axial hydroxy group at C-4 was converted into the methane-6 and the p-toluenesulphonate 7 6 and 7, respectively; the corresponding trifluoromethanesulphonate was also prepared 8 , but proved to be too unstable in the following reactions using lithium dimethylamide or sodium azide in DMF at 0 °C, respectively. Under the latter conditions however, 6 and 7 could easily be transformed into the corresponding azide 8.…”
Section: Resultsmentioning
confidence: 99%